Psychicones: Visual Traces of the Soul in Late Nineteenth-Century Fluidic Photography. Issue 3 (13th June 2016) - Pethes, Nicolas
Abstract : The article discusses attempts to visualise the soul on photographic plates at the end of the nineteenth century, as conducted by the French physician Hippolyte Baraduc in Paris. Although Baraduc refers to earlier experiments on fluidic photography in his book on The Human Soul (1896) and is usually mentioned as a precursor to parapsychological thought photography of the twentieth century, his work is presented as a genuine attempt at photographic soul-catching. Rather than producing mimetic representations of thoughts and imaginations, Baraduc claims to present the vital radiation of the psyche itself and therefore calls the images he produces psychicones . The article first discusses the difference between this method of soul photography and other kinds of occult media technologies of the time, emphasising the significance of its non-mimetic, abstract character: since the soul itself was considered an abstract entity, abstract traces seemed all the more convincing to the contemporary audience. Secondly, the article shows how the technological agency of photography allowed Baraduc's psychicones to be tied into related discourses in medicine and psychology. Insofar as the photographic plates displayed actual visual traces, Baraduc and his followers no longer considered hallucinations illusionary and pathological but emphasised the physical reality and normality of imagination. Yet, the greatest influence of soul photography was not on science but on art. As the third part of the paper argues, the abstract shapes on Baraduc's plates provided inspiration for contemporary avant-garde aesthetics, for example, Kandinsky's abstract paintings and the random streams of consciousness in surrealistic literature.